The other side of Redwall : medieval othering and binary oppositions in The Outcast of Redwall - Quah, Christopher Wai Kheong; Anita Harris Satkunananthan; Ravichandran Vengadasamy (Penerbit Universiti Kebangsaan Malaysia, 2021)
Brian Jacques’s Redwall series of anthropomorphic fantasy novels featuring animals divided into the noblebeast and vermin are well-loved, with the medieval images of Redwall Abbey, Mossflower and other noblebeast communities exciting the imagination of its readers. Nevertheless, there exists a binary opposition of the noblebeast and the vermin who are vilified and portrayed as savage and amoral. This article argues that the orientalistic roots of twentieth century fantasy novels which are based on a nostalgia for medieval times is a main impetus for the Orientalism present in Outcast of Redwall. Concomitantly, in this article, the analysis of Outcast of Redwall interrogates instances of Orientalism in the novel through a literary postcolonial framework, connecting Orientalism to the idea of the Other and the Self. Specifically, the character of Veil in Outcast of Redwall is analysed, looking at the ways in which he fails to be assimilated in the medieval society of Redwall because of his vermin heritage. The findings from this article reveal that Orientalism is baked into the Redwall novels and how the depiction of the vermin correlate with the ways in which the West conceived of the Orient from the age of colonial exploration and beyond, a legacy of the ways in which the twentieth century fantasy novel derived much of its inspiration from a medieval aesthetic that incorporates binary oppositions and a fear of the Other.